In-network data storage protocols for wireless sensor networks: A state-of-the-art survey - Kais Mekki; William Derigent; Eric Rondeau; André Thomas (International Journal of Distributed Sensor Networks)
In wireless sensor networks, the aim of storage protocols is to efficiently replicate data across nodes and to improve data collection and querying by sinks. Among them, in-network storage protocols replicate data in a set of nodes that depends on some characteristics such as network topology and geographic location. Researchers have proposed various techniques to implement in-network storage. In this article, we summarize and highlight the key ideas of existing protocols which are further classified into three categories (reactive, unstructured proactive, and structured proactive) based on topology, load balancing, transmission strategy, and reliability. Benefits and drawbacks of each protocol are studied and compared with different requirements. Finally, future research directions are provided for efficient in-network storage in wireless sensor network.